TRAINING TECHNOLOGY OF THE FUTURE ELEMANTARY SCHOOL TEACHER - Faxriddin Shodiyev (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article discusses the issues of training innovative and creative modern future primary school teachers in the spirit of high spirituality and patriotism, the formation of technology of competitive tasks and responsibilities of young professionals in the global process, and improving the education system to international standards.